Pengaruh Kebijakan Pilkada Masa Pandemi Terhadap Tingkat Partisipasi Masyarakat pada Pemilihan Kepala Daerah di Kota Sungai Penuh Tahun 2020 - Vika Yvanka; M. Fachri Adnan (Jurnal Teori dan Riset Administrasi Publik, 2022)
This research is based on the differences in the implementation of the Pilkada during the pandemic and the increasing participation of the people of Sungai Penuh city in the 2020 Pilkada compared to the public participation in the 2015 election, which increased by 3,889 people from the number of registered DPTs. Considering that Indonesia is facing a non-natural disaster, namely the COVID-19 pandemic with many regulations, policies and restrictions set by the government. This study aims to see the effect of the regional election policy during the pandemic on public participation in the elections of Sungai Penuh City. The reason for choosing the city of Sungai Penuh as the research location is because the city of Sungai Penuh is included in the 5 cities with the highest level of vulnerability according to the Bawaslu of Jambi Province. The research method used in this research is quantitative, combined with associative methods. Collecting data using a questionnaire method to respondents consisting of 156 people who were randomly assigned from 8 sub-districts in the city of Sungai Penuh. Data analysis used classical assumption test, partial test and simple linear test using SPSS Software Version 22.0. The results of this study indicate that the pilkada policy during the Covid-19 pandemic in the implementation of the 2020 elections had a significant effect on the level of participation of the people of Sungai Penuh city as much as 42.2%.